It takes two to seesaw: How students of foreign origin experience Icelandic primary school - Gunnþórsdóttir, Hermína; Aradóttir, Lilja Rós (Menntavísindasvið Háskóla Íslands, 2021)
In a multicultural society, families are as varied as they are many. This diversity cannot be traced to different cultural or religious backgrounds alone; family structures also vary. Börkur Hansen and Hanna Ragnarsdóttir (2010) point out that not only immigrants bring diversity to communities, as no two individuals are the same and diversity lies in the very nature of human societies. Since the beginning of the 21st century, Icelandic society has changed rapidly, as the ratio of the country’s inhabitants who are defined as immigrants has grown from 2.6% in the year 2000 to 15% in 2020 (Hagstofa Íslands [Iceland Statistics], n.d.).The growing number of children of foreign origin in Icelandic schools has given wings to the ideology of a multicultural school and pedagogy. Those ideas have gained ground in step with theories relating to inclusive education and the importance of ensuring the equality of minority groups and marginalised individuals (Nieto, 2010). An education policy promoting the ideology of the inclusive school has its foundation in general human rights, focusing on the situation of marginalised groups within the schools. It is a fundamental concern that the schools be neither adapted to the needs of certain social classes, nor characterised by their dominant perceptions (Sko?la- og fri?stundasvið Reykjavi?kurborgar [Reykjavík Municipality School and Recreation Department], 2012).The Icelandic national curriculum guide for compulsory schools (Mennta- og menningarmálaráðuneytið [Ministry of Education, Science and Culture], 2013) expresses a similar understanding of the concept of the inclusive school:Inclusive school means a compulsory school in the pupils’ municipality or local community where the educational and social requirements of each pupil are met with emphasis on respect for human values and social justice (p. 41)Icelandic research has shown that students of foreign origin are often socially isolated, they feel worse than their peers, have fewer friends, are more likely to be bullied and are ...